2013
DOI: 10.1155/2013/826435
|View full text |Cite
|
Sign up to set email alerts
|

From Notochord Formation to Hereditary Chordoma: The Many Roles ofBrachyury

Abstract: Chordoma is a rare, but often malignant, bone cancer that preferentially affects the axial skeleton and the skull base. These tumors are both sporadic and hereditary and appear to occur more frequently after the fourth decade of life; however, modern technologies have increased the detection of pediatric chordomas. Chordomas originate from remnants of the notochord, the main embryonic axial structure that precedes the backbone, and share with notochord cells both histological features and the expression of cha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
72
0
1

Year Published

2014
2014
2017
2017

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 86 publications
(73 citation statements)
references
References 175 publications
0
72
0
1
Order By: Relevance
“…Our results show the presence of two distinct MPC populations in the tailbud: one that contributes to hypochord and notochord and a second that gives rise to notochord and floor plate. This work will provide insight into poorly understood human diseases associated with defective notochord development, including SNS and the rare but highly lethal cancer chordoma (Nibu et al, 2013;Yazici et al, 2014). Chordoma is an aggressive tumor type found along the axis of the body, and is thought to be derived from notochord remnants that persist from embryonic stages into adulthood (Nibu et al, 2013).…”
Section: Discussionmentioning
confidence: 99%
“…Our results show the presence of two distinct MPC populations in the tailbud: one that contributes to hypochord and notochord and a second that gives rise to notochord and floor plate. This work will provide insight into poorly understood human diseases associated with defective notochord development, including SNS and the rare but highly lethal cancer chordoma (Nibu et al, 2013;Yazici et al, 2014). Chordoma is an aggressive tumor type found along the axis of the body, and is thought to be derived from notochord remnants that persist from embryonic stages into adulthood (Nibu et al, 2013).…”
Section: Discussionmentioning
confidence: 99%
“…As the name implies, chordomas are thought to be of notochordal origin and one of the major roles of T is in the development of the notochord (Nibu et al, 2013). T has also been implicated in controlling EMT in some cancers such as adenoid cystic carcinoma and colorectal cancer (Sarkar et al, 2012;Shimoda et al, 2012).…”
Section: Cip1mentioning
confidence: 99%
“…Numerous subsequent studies confirmed that the coordinated expression of the T gene during gastrulation is essential for appropriate notochord, neural tube, and mesoderm development (Chesley 1935;Pennimpede et al 2012;Satoh et al 2012). Recently, the T gene has gained interest because of its association with the human chordoma, a sporadic and hereditary tumor originating from relicts of the notochord (Yang et al 2009;Pillay et al 2012;Nibu et al 2013). Thus, the T gene is a prime candidate for investigating phenotypic alterations of the vertebral column and spinal cord.…”
mentioning
confidence: 99%